The impact of collaborative pain management by healthcare providers on sleep quality and self-efficacy in perioperative lumbar surgery patients - Li, Jucai; Song, Yanli; Zhao, Yixin; Su, Dan; Li, Meina; Zhao, Shu’e (Scientific reports, 2025)
The present study aimed to investigate the effects of collaborative pain management by healthcare providers on sleep quality and self-efficacy in perioperative lumbar disc herniation patients. A total of 300 lumbar disc herniation patients admitted to our hospital from February 2022 to February 2023 were selected as the research subjects. They were divided into a study group (receiving collaborative pain management by healthcare providers) and a control group (receiving conventional pain management), with 150 patients in each group. Surgical parameters, pain levels at different time points, as well as pre- and post-intervention pain levels, sleep quality, self-efficacy, lumbar function, patients’ satisfaction, and psychological status were compared between the two groups. There were no significant differences between the two groups in terms of gender, age, smoking, alcohol consumption, body mass index, disease duration, type and location of lumbar disc herniation, and comorbidities ( P > 0.05). Surgical duration, blood loss, and time to first meal did not significantly differ between the two groups ( P > 0.05). However, the study group had significantly shorter times to first ambulation, first gas passage, first bowel movement, and length of hospital stay compared to the control group ( P < 0.05). Pre-intervention comparisons of pain levels showed no significant differences between the two groups ( P > 0.05). Postoperatively, at 12, 24, 48, and 72 h, the study group had lower pain levels than the control group, with statistically significant differences ( P < 0.05). Pre-intervention comparisons of daytime dysfunction, hypnotic drug use, sleep disturbances, sleep efficiency, sleep duration, time to fall asleep, and sleep quality revealed no significant differences between the two groups ( P > 0.05). However, post-intervention, the study group exhibited significantly lower PSQI scores in daytime dysfunction, hypnotic drug use, sleep disturbances, sleep efficiency, sleep duration, time to fall asleep, and sleep quality compared to the control group ( P < 0.05). Pre-intervention comparisons of pain management, physical function, and symptom coping showed no significant differences between the two groups ( P > 0.05). After intervention, the study group demonstrated significantly better pain management, physical function, and symptom coping compared to the control group ( P < 0.05). Before the intervention, subjective symptoms, bladder function, daily activity limitation, and clinical signs showed no significant differences between the two groups ( P > 0.05). After the intervention, however, the study group exhibited significantly better subjective symptoms, bladder function, reduced daily activity limitation, and clinical signs compared to the control group ( P < 0.05). Before the intervention, there were no significant difference in patients’ satisfaction, anxiety score, and depression score between the two groups ( P > 0.05). After the intervention, the study group showed lower anxiety score and depression score, and higher satisfaction with the nursing intervention compared to the control group (all P < 0.05). Collaborative pain management by healthcare providers can effectively improve sleep quality and enhance self-efficacy in perioperative lumbar surgery patients, and holds promise for clinical application.